2007
DOI: 10.1007/s10585-007-9132-4
|View full text |Cite
|
Sign up to set email alerts
|

CNTO 95, a fully human anti αv integrin antibody, inhibits cell signaling, migration, invasion, and spontaneous metastasis of human breast cancer cells

Abstract: CNTO 95 is a fully human monoclonal antibody that recognizes alphav integrins. Previous studies have shown that CNTO 95 exhibits both anti-tumor and anti-angiogenic activities (Trikha M et al., Int J Cancer 110:326-335, 2004). In this study we investigated the biological activities of CNTO 95 on breast tumor cells both in vitro and in vivo. In vitro treatment with CNTO 95 decreased the viability of breast tumor cells adhering to vitronectin. CNTO 95 inhibited tumor cell adhesion, migration, and invasion in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 33 publications
(43 reference statements)
4
74
1
3
Order By: Relevance
“…Although the antiangiogenic and radiosensitizing effects of intetumumab are not unique, intetumumab has the added advantage over many other antiangiogenic agents in development, such as inhibiting the development of metastases by targeting the αv integrin receptors and blocking its downstream cell adhesion signaling pathway (4). Here, we further show the ability of intetumumab to inhibit the subsequent development of pulmonary metastases in the NSCLC A549 model following either i.v.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the antiangiogenic and radiosensitizing effects of intetumumab are not unique, intetumumab has the added advantage over many other antiangiogenic agents in development, such as inhibiting the development of metastases by targeting the αv integrin receptors and blocking its downstream cell adhesion signaling pathway (4). Here, we further show the ability of intetumumab to inhibit the subsequent development of pulmonary metastases in the NSCLC A549 model following either i.v.…”
Section: Discussionmentioning
confidence: 62%
“…Preclinical studies have shown that intetumumab exhibits antiangiogenic and antitumor activity in human cancer xenograft models in nude mice (1)(2)(3). Intetumumab has been reported to inhibit cell adhesion, migration, invasion, and proliferation of endothelial cells and tumor cells in vitro and tumor metastasis in vivo in nude mice with human breast cancer xenografts by inactivating the focal adhesion kinase (FAK) and the docking protein paxillin (1,4). We have previously shown that intetumumab is a potential radiation sensitizer when used in combination with fractionated radiation therapy in human cancer xenograft models in nude mice (5).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ␣v␤3 and ␣v␤6 could be the targets because both of them act as the important receptors for fibronectin, and both of them are deeply implicated in the promotion of the cancer cell metastasis (52)(53)(54)(55). One more important molecule that could not be ignored is E-cadherin, which plays critical roles in cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the antibodies in development or currently marketed recognize membraneassociated antigens (28,32,37,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80). Interaction of antibodies with this class of target antigen can greatly impact their PK.…”
Section: Introductionmentioning
confidence: 99%